Tinkering Epistemology with Ontology: Reformulating Popper’s Reformulation of the Problem of Induction with Eastern and Western Ontology - Chen, Szu-Ting (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2023)
Karl Popper thought that he had successfully resolved the philosophical problem of induction by replacing inductive logic with deductive logic in every aspect of the philosophical analysis of science. In examining Popper’s approach, it may seem, however, that, instead of resolving the original problem, what he has resolved was a reformulated problem of induction. Nevertheless, by “reformulating” Popper’s reformulation by using the relevant ontology from contemporary Eastern and Western philosophers, this paper maintains that this re-reformulated meta-account can be used to argue that the first impression that the problem has not been resolved can be replaced with the idea that Popper’s reformulation of the problem of induction into the problem of scientific growth has its meaning in a contemporary context. The key significance of this reformulation is: By examining the paired concepts—such as “inductive inference vs. deductive inference” or “context of discovery vs. context of justification”—from the perspective that “scientific reasoning is to find a stable causal environment or situation to derive regular causal conclusions”, we can then maintain that instead of regarding these concepts as mutually exclusive in the “practice of causal inquiry”, it is better to assume that they have a complementary relationship—this situation manifests exactly what Popper believed: In the process of scientific inquiry, there is always a dynamic interdependence between conjecture and refutation.